Assessing local instrument reliability and validity: A field-based example from northern Uganda - Betancourt, Theresa; Bass, Judith; Borisova, Ivelina; Neugebauer, Richard; Speelman, Liesbeth; Onyango, Grace; Bolton, Paul (Social psychiatry and psychiatric epidemiology, 2009)
This paper presents an approach for evaluating the reliability and validity of mental health measures in non-Western field settings. We describe this approach using the example of our development of the Acholi Psychosocial Assessment Instrument (APAI), which is designed to assess depression-like (two tam, par and kumu), anxiety-like (ma lwor) and conduct problems (kwo maraco) among waraffected adolescents in northern Uganda. To examine the criterion validity of this measure in the absence of a traditional gold standard, we derived local syndrome terms from qualitative data and used self reports of these syndromes by indigenous people as a reference point for determining caseness. Reliability was examined using standard test-retest and inter-rater methods. Each of the subscale scores for the depression-like syndromes exhibited strong internal reliability ranging from α =0.84 to 0.87. Internal reliability was good for anxiety (0.70), conduct problems (0.83), and the pro-social attitudes and behaviors (0.70) subscales. Combined inter-rater reliability and test-retest reliability were good for most subscales except for the conduct problem scale and prosocial scales. The pattern of significant mean differences in the corresponding APAI problem scale score between self-reported cases vs. noncases on local syndrome terms was confirmed in the data for all of the three depression-like syndromes, but not for the anxiety-like syndrome ma lwor or the conduct problem kwo maraco.
Keywords: War; Adolescents; Northern Uganda; Mental health; Validity